Programmed hepatocytes cell death associated with FLIP downregulation in response to extracellular PreS1/2. Issue 3 (19th November 2013) - Rojas, Masyelly D.; Peterson, Darrell L.; Barboza, Luisa; Terán‐Ángel, Guillermo; Labastida‐Moreno, Cesar A.; Berrueta, Lisbeth; Salmen, Siham
Abstract Chronic hepatitis B virus (HBV) infection involves liver damage resulting in continuous cell injury and death. During HBV infection, hepatocytes exhibit changes in death receptor expression and in their susceptibility to death. These changes are observed not only in infected cells but also in bystander cells. Because excess viral surface protein (HBsAg) is secreted in large amounts as soluble particles containing preS proteins, the role of soluble preS1/2 in hepatocyte (HepG2) death modulation is an important issue to be explored. An increase of cell death induced by preS1/2 was observed. Also, cell death was associated with the down‐regulation of FLIP and activation of caspase 8, caspase 9, and BID. Additionally, hepatocytes exhibited a sensitization to death mediated by the Fas receptor. These results, may contribute to understanding the role of envelope proteins (preS1/2) in the pathogenesis of HBV infection. J. Med. Virol. 86:496–504, 2014. © 2013 Wiley Periodicals, Inc.